The Tokenization of Illiquid Assets: Architecting the Next Generation of Investment Banking Advisory and Capital Markets - Ayoola Olamilekan Sikiru; Onyeka Kelvin Chima; Mary Otunba; Olatunde Gaffar; Adedoyin Adeola Adenuga (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The landscape of investment banking and capital markets is undergoing a radical transformation, driven by the convergence of blockchain technology and decentralized finance (DeFi). At the heart of this evolution is the tokenization of illiquid assets—a process that converts ownership rights in traditionally non-tradable assets such as real estate, art, private equity, and infrastructure into digital tokens recorded on a blockchain. This innovation offers the promise of increased market accessibility, improved liquidity, enhanced transparency, and operational efficiency. By lowering entry barriers and reducing friction in asset transfer, tokenization is reshaping the traditional paradigms of advisory services and capital raising, especially for mid-market and emerging market issuers. This paper explores how investment banks are beginning to redefine their advisory models and underwriting strategies in response to the growing demand for tokenized securities. It examines regulatory challenges, the evolving investor landscape, and the technical infrastructure required to support these novel instruments. With a focus on developments through 2024, the paper synthesizes global case studies, including efforts by banks, fintechs, and digital asset exchanges to build compliant platforms for token issuance, custody, and secondary trading. Furthermore, it analyzes the intersection of tokenization with Environmental, Social, and Governance (ESG) objectives, assessing how digital assets can support greater accountability and reporting efficiency. From a capital markets perspective, tokenization offers an opportunity to unbundle traditional services, allowing for fractional ownership, 24/7 trading, automated compliance, and programmable assets. These shifts not only require a new technological architecture but also demand an evolution in legal frameworks and investor protections. Investment banks, thus, face a critical juncture: to either adapt and lead in developing tokenization-enabled capital markets or risk disintermediation by more agile digital-native competitors. This paper proposes a strategic blueprint for how advisory and deal structuring functions can evolve to meet these emerging demands, while also offering policy recommendations for building secure, scalable, and inclusive tokenization ecosystems.